2017
DOI: 10.1080/01635581.2017.1299872
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Antioxidants: Potential Anticancer Agents

Abstract: There are several extrinsic and intrinsic factors involving reactive oxygen species that play critical roles in tumor development and progression by inducing DNA mutations, genomic instability, and aberrant pro-tumorigenic signaling. There are various essential micronutrients including minerals and vitamins in the diet, which play pivotal roles in maintaining and reinforcing antioxidant performance, affecting the complex network of genes (nutrigenomic approach) and encoding proteins for carcinogenesis. A lot o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 86 publications
2
30
1
Order By: Relevance
“…The animal model study further demonstrated that feeding Apc/Kras G 12 D mutant mice high-dose ascorbic acid may impair tumor growth (Yun et al, 2015 ). Consistent with the data reported by Yun et al ( 2015 ) and Ma Y. et al ( 2014 ), Wu et al ( 2017 ) identify an antitumor activity of ascorbic acid in a clinical study. Although the molecular link underlying ascorbic acid and anticancer activity require further elucidation, most of the experimental studies indicate that modulating oxidative stress could play a crucial role (Badgujar et al, 2015 ; Huang et al, 2017 ).…”
Section: Role Of Antioxidants In the Prevention Of Age-related Diseassupporting
confidence: 83%
“…The animal model study further demonstrated that feeding Apc/Kras G 12 D mutant mice high-dose ascorbic acid may impair tumor growth (Yun et al, 2015 ). Consistent with the data reported by Yun et al ( 2015 ) and Ma Y. et al ( 2014 ), Wu et al ( 2017 ) identify an antitumor activity of ascorbic acid in a clinical study. Although the molecular link underlying ascorbic acid and anticancer activity require further elucidation, most of the experimental studies indicate that modulating oxidative stress could play a crucial role (Badgujar et al, 2015 ; Huang et al, 2017 ).…”
Section: Role Of Antioxidants In the Prevention Of Age-related Diseassupporting
confidence: 83%
“…59 Moreover, organic acids present in natural matrices are involved in the reduction of oxidative stress. 60 Phenolic compounds which contribute directly to antioxidative protection and play an important role in stabilizing lipid peroxidation were also determined in the studied sample, 11 being identified as p-hydroxybenzoic acid and p-coumaric acid (Table 2). Similarly, Fernandes et al 24 described p-hydroxybenzoic acid as the main phenolic acid in samples of P. squamosus of different origins, while cinnamic acid, a phenolic-related compound, was also found in small amounts.…”
Section: Chemical Composition Of Polyporus Squamosusmentioning
confidence: 99%
“…Polyphenols are the most studied nutraceuticals so far and many beneficial effects on various diseases have been reported in the literature, along with the problems and limits related to their use as drugs [ 30 ]. We refer to recent reviews for their anti-cancer effects, as they are able to modulate multiple coding and non-coding genes, ultimately targeting the main hallmarks of cancer [ 31 , 32 , 33 , 34 , 35 ].…”
Section: Nutraceuticalsmentioning
confidence: 99%